Free Trade Area Membership as a Stepping Stone to Development : The Case of ASEAN - Fukase, Emiko; Martin, Will (Washington, DC: World Bank, 2013)
This study investigates the economic impacts of accession to the ASEAN Free Trade Area (AFTA) by the new member countries of Cambodia, the Lao PDR, Myanmar, and Vietnam. The trade policies of these countries are examined, and a series of quantitative analyses were undertaken to evaluate the impacts of accession. The results showed that the static impacts of reducing tariffs against ASEAN members are beneficial, although the magnitude of the net gains is diminished by the trade diversion resulting from the discriminatory nature of the reforms. The binding commitments on protection rates under the AFTA plan provide an important initial step to more broader and more beneficial trade reforms. The study focuses on some of the key country-specific policy challenges associated with trade liberalization--such as declining tariff revenues in Cambodia, and the negative impacts on sensitive domestic industries in Vietnam. The study recommends that accession to AFTA be viewed as an important transitional step in the broader process of trade reform and institutional development needed for successful development and poverty alleviation.